Investment Under Uncertain Market Conditions - Sakellaris, Plutarchos (The Review of Economics and Statistics, 1995)
This paper studies the responsiveness of firm investment to shocks in the input factor and output prices (the market conditions) by using stock market information on excess returns. The 'q' theory of investment is modified to allow for heterogeneous capital, ex post inflexible technology, and irreversible investment. A structural model linking the excess returns to a firm's equity to the firm's investment history and the evolution of the market conditions is estimated using a panel of U.S. manufacturing firms. The estimates of the cost of adjusting tile capital stock are economically sensible. They imply a high degree of sensitivity of investment to fundamental variables that affect the profitability of capital such as the market conditions and the purchase price of capital. Copyright 1995 by MIT Press.